Antecedents of e-satisfaction, e-trust and their impact on purchase intention on Tokopedia MSME Buyers consumers - Stevanus Satrio Anggorogiri (Enrichment : Journal of Management, 2022)
Along with the increasing number of social media and internet users in Indonesia, encouraging the emergence of various real solutions that have an impact on shifting the map of the Indonesian national economy. However, with the entry of the pandemic into Indonesia, many MSMEs were unable to survive. This encourages MSME business actors to digitize by joining one of the e-commerce stores, Tokopedia, to continue to survive. This study aims to analyze the antecedents that can affect electronic satisfaction (E-satisfaction), electronic trust (e-trust), and their impact on purchase intention (purchase intention) on Tokopedia consumers who buy MSME products. The sampling method in this study used purposive sampling with the analysis method of partial least squares equation modelling (PLS-SEM) to 190 respondents. The results of this study indicate that the antecedents consisting of variables perceived ease of use, perceived usefulness and social media marketing have a significant positive influence on purchase intention through e-satisfaction and e-trust mediation.